2023
DOI: 10.2196/44179
|View full text |Cite
|
Sign up to set email alerts
|

Cardio4Health Study, a Cardiac Telerehabilitation Pilot Program Aimed at Patients After an Ischemic Event: Cross-sectional Study

Abstract: Background Center-based cardiac rehabilitation programs (CRPs) reduce morbidity and mortality after an ischemic cardiac event; however, they are widely underused. Home-based CRP has emerged as an alternative to improve patient adherence; however, its safety and efficacy remain unclear, especially for older patients and female patients. Objective This study aimed to develop a holistic home-based CRP for patients with ischemic heart disease and evaluate i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Psychological complaints were measured in 11 of the 22 studies. 22,23,25,27,31–34,3739 Anxiety and depression were measured in six studies, and most of them found no differences in the scores for anxiety and depression 23,24,29,30,34,38 except one study. 34 The participants’ sense of individuality, autonomy, capability and motivation improved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Psychological complaints were measured in 11 of the 22 studies. 22,23,25,27,31–34,3739 Anxiety and depression were measured in six studies, and most of them found no differences in the scores for anxiety and depression 23,24,29,30,34,38 except one study. 34 The participants’ sense of individuality, autonomy, capability and motivation improved.…”
Section: Resultsmentioning
confidence: 99%
“…1839 The studies varied in research designs, including 11 randomized controlled trials, 1820,23,26,27,3033,35 five pilot studies, 21,24,25,28,36 two observational studies, 29,34 one case study, 22 one qualitative study, 37 one mixed-method study, 38 and one cross-sectional study. 39 The studies had been conducted in different locations: 11 of them in Europe, 1820,22,28,31,3336,39 six in Asia, 23,24,29,30,32,37 three in Australia, 2527 and two in North America. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations